Educational Transformation Through the Implementation of an Edupreneurial Business Model (International Journal of Education and Literature, 2025)
Educational transformation in the era of globalization and the Industrial Revolution 4.0 requires educational institutions not only to produce academically competent graduates but also individuals with entrepreneurial spirit, creativity, and adaptability. The high rate of educated unemployment indicates the need for alternative approaches, one of which is the implementation of an edupreneurial business model. This concept integrates entrepreneurial principles into educational management, emphasizing innovation, value creation, and sustainability. This study analyzes the application of business models in edupreneurship within formal educational institutions, covering conventional, digital, and social models. The findings indicate that edupreneurship enhances educational relevance, expands accessibility, and supports financial independence of institutions. Social edupreneurship is considered effective in promoting educational equity through socially impactful business models. The success of implementing an edupreneurial business model depends on continuous innovation, technological utilization, strategic partnerships, and diversification of funding sources. Therefore, edupreneurship is recommended as a visionary, adaptive, and sustainable strategy for educational transformation.